2022
DOI: 10.1177/0044118x221077712
|View full text |Cite
|
Sign up to set email alerts
|

Why are Some Victims Also Bullies? The Role of Peer Relationship Management and Anger Regulation in Traditional Bullying

Abstract: There is ample evidence of bullying victimization-perpetration association. However, little is known about the role of socioemotional variables in reinforcing or mitigating it. There is a need to delve deeper into what victims feel and do that leads them to bully. This study aimed to analyze the moderating role of peer relationship management and anger regulation in the victimization-perpetration association, controlling gender and age. This cross-sectional study involved 874 Spanish middle school students (47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…It has been further explained that individuals with strong social competencies were less prone to provocation related to anger and subsequently to aggression in conflict settings. To prove the importance of developing social competences in order to manage anger attitudes related to psychological distress, literature reviews [ 50 , 51 ] successfully implemented Social Skills Training (SST) as a treatment option for reinforcement of prosocial behavior to decrease risks of anger responses in social settings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been further explained that individuals with strong social competencies were less prone to provocation related to anger and subsequently to aggression in conflict settings. To prove the importance of developing social competences in order to manage anger attitudes related to psychological distress, literature reviews [ 50 , 51 ] successfully implemented Social Skills Training (SST) as a treatment option for reinforcement of prosocial behavior to decrease risks of anger responses in social settings.…”
Section: Discussionmentioning
confidence: 99%
“…These were later applied to cyberbullying, and the core roles in cyberbullying behavior are perpetrators, victims, and bystanders ( Musharraf and Anis-ul-Haque, 2018 ; Moxey and Bussey, 2019 ). Importantly, the cyberbullying perpetrator and the victim are interchangeable, in which victims used cyberbullying as a way to protect themselves, and thus, plus a new role, the cyber bully–victim, who are both cyberbullying victims and cyberbullying perpetrators ( McInroy and Mishna, 2017 ; Espino et al, 2022 ). Regarding cyberbullying perpetrators and victims, researchers agreed that perpetration and victimization co-occur far more frequently in cyberspace than in the offline setting, because offensive messages spread quickly online ( Musharraf and Anis-ul-Haque, 2018 ; Clark and Bussey, 2020 ; Parti et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cyberbullying perpetrators and victims, researchers agreed that perpetration and victimization co-occur far more frequently in cyberspace than in the offline setting, because offensive messages spread quickly online ( Musharraf and Anis-ul-Haque, 2018 ; Clark and Bussey, 2020 ; Parti et al, 2022 ). Meanwhile, Espino et al (2022) showed that if cyberbullying victims have experienced frequent aggression, they are more likely to perpetrate cyberbullying. These points show that we shall consider the challenges when the aspects of traditional bullying features directly applied in cyberbullying ( Slonje et al, 2013 ), and cyberbullying is an interaction that could be predicted and prevented through interpersonal relationships ( Varela et al, 2018 ; Mehari and Basu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is still not clear why some students become bully-victims ( Malamut & Salmivalli, 2021 ), previous studies showed that traits like reduced empathy, limited prosocial behavior, fragile family bonds, or difficulties in anger regulation could contribute to their profile ( Chan & Wong, 2015 ; Espino, Guarini, Menabò, & Del Rey, 2023 ). Bully-victims are the most disliked group, and they are more likely to have higher levels of depression and self-harm compared to the other groups ( Georgiou & Stavrinides, 2008 ).…”
mentioning
confidence: 99%